The TKT (Teaching Knowledge Test) course - Spratt, Mary; Pulverness, Alan; Williams, Melanie (Cambridge Cambridge University press, 2010)
This is the teacher training course for teachers and trainee teachers preparing fot the TKT. A extensive introduction to ELT methodology, a range of tasks and three complete practice tests in one book provides a comprehensive package for TKT candidates.
Contents.
Keywords: Teaching; Teacher trainers; Classroom Techniques; English - foreign language; Methodology